The Short Stories of F. Scott Fitzgerald A New Collection - Fitzgerald, F. Scott (Francis Scott), 1896-1940. (New York, Scribner, 1989)
"The 43 stories in this collection include both the famous ones and several that are less well known." Booklist. "Collection of 43 short stories that illustrate Fitzgerald's depth and range of literary talent ... including commercial work for the Saturday Evening Post."
Keywords: United States -- Social life and customs -- 20th century -- Fiction